Faktor dan kesan masalah membaca dalam kalangan murid sekolah rendah kerajaan di Brunei Darussalam - Tamam Timbang,; Zambri Mahamod,; Afendi Hamat, (Penerbit UKM, 2011)
This research to study the factors and effective reading problem among the primary pupils from the government schools encounter in Negara Brunei Darussalam. The qualitative method that used multicase multiplesite approach. The participant which included four pupils, four parents and six teachers from four different primary schools in Brunei Darussalam, were interviewed in depth. The Nvivo 7 software used to analyze the data. The findings were reported in two parts; the profiles of the schools and participants in the research, as well as the report on the questionnaires. From this research, it is found that the factors that contribute to the inability to read efficiently in the government school primary students are: (a) individual factor, (b) psychological factor, (c) method of teaching, (d) lesson periods, (e) environmental factor, and (f) text books. The five effective readings problem there was found: (i) fill in examination, (ii), to effect another subject, (iii) problems in examination, (iii) psychology effect, and (v) nombor of position in class. The implication study are language teacher teaching methode to improve to settle readings problem among school pupils at Brunei Darussalam